Study of the scattering of 15C at energies around the Coulomb barrier. (December 2020) - Ovejas, J D; Knyazev, A; Martel, I; Tengblad, O; Borge, M J G; Cederkall, J; Keeley, N; Rusek, K; García-Ramos, C; Pérez, T; Acosta, L A; Arokiaraj, A A; et al.
Abstract: The neutron rich carbon isotope 15 C is the only known case of an almost "pure" 2s1/2 single-neutron halo ground state configuration. At collision energies around the Coulomb barrier the reaction dynamics is expected to be dominated by single neutron transfer and breakup. To investigate these effects, we have measured the scattering of 15 C with a 208 Pb target at 65 MeV at the HIE-ISOLDE facility in CERN (Geneva, Switzerland). The preliminary data demonstrates the presence of a strong long-range absorption pattern in the angular distribution of the elastic cross section. The results are discussed in the framework of Optical Model calculations.